Development of community participation based on behaviour in managing participative programs - Dedy Hermawan; Simon Sumanjoyo Hutagalung (Faculty of Social and Political Science, Universitas Airlangga, 2019)
The government uses the participation approach in the efforts to overcome the socio-economic problem capacity within the community since it was able to increase community empowerment indirectly, even though to the probability of fake participation in the program implementation still exist. The purpose of this research is to find out the participation form that raised by the government programs, by looking at the community behaviour factors that determine the success of participation and a behaviour-based model of community participation to overcome the participation problem. The research type is descriptive with a qualitative approach through the application of several methods of data collection, in-depth interviews, secondary data studies and observations. The informants of this study were 20 people from local government, program implementers and target groups. The analysis data is using the qualitative technique. The results identified the typology of participation that emerged in the management of community participation programs in Lampung Province in the area of non-participation, delegation of authority and partnerships. The conditions of participation that occur driven by community behaviour factors. Consist of three factors, namely: 1) Trust or opportunity to participate; 2) Ability to participate, and 3) Willingness to participate in each activity determined by the presence or absence of the interests concerned. In the end, a behaviour-based participation management model built by adopting the concept of community engagement and personal engagement.